Sistem Auto Resume Pada 3D Printer - Muhammad Nur; Mukhlidi Muskhir (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Three-dimensional (3D) printing technology has progressed rapidly and is very popular in the manufacturing industry. 3D printing is a tool that can print three-dimensional objects from a three-dimensional design that has volume. Sudden power outages or momentary fluctuations in power supply (flicker) are a serious problem when 3D printing is in operation, so one cannot know where and how to restart it when the power goes out for a moment. Mini UPS is a mini-sized UPS (Uninterruptible Power Supply) that functions as temporary electrical power to continue the performance process of a device. In this research, we will discuss the use of a mini UPS for the Auto Resume system on a 3D Printer so that it can continue the printing process without having to restart when the power goes out for a moment.